Tidal Modulation of Hydrothermal Tremor: Examples From Ischia and Campi Flegrei Volcanoes, Italy - Petrosino, Simona; Dumont, Stéphanie (Frontiers in Earth Science, 2022)
Volcano dynamics results from an interplay between internal and external processes spanning different time scales. Unravelling how such processes interact may provide key insights into the mechanisms that may lead to the destabilization of the volcanoes and eruption, a critical information to forecast hazards. Studies dealing with tidal influence on volcanoes fall within this context, yet the cause-effect relationship between tides and eruptions is still poorly understood. In the present study, we investigate the tidal influence on two nearby volcanoes, Ischia and Campi Flegrei (Italy), characterized by intense hydrothermal activity. We analyze the seismic tremor of hydrothermal origin recorded by four seismic stations between January and June 2020 by using Singular Spectrum Analysis. We detect up to five long term tidal periodicities ranging from ∼5 to ∼29 days. The results indicate that the seismic tremor is modulated by Earth tides at both volcanoes. In addition, differences in phase and amplitude modulation between the response of both hydrothermal systems to tidal forcing reveal specific features related to the tremor source and to properties of the surrounding medium. These phenomena indicate an interplay between solid Earth and the dynamics of these two volcanoes. Similar approaches on hydrothermal systems at volcanoes would contribute to better characterize the hydrothermal circulation and their evolving conditions that may represent a precursor of a new phase of activity.